Interpolating Between Li-Yau's and Hamilton's Harnack Inequalities on a Surface (Journal of Partial Differential Equations, 1998)
We establish a one-parameter family of Harnack inequalities connecting Li and Yau's differential Harnack inequality for the heat equation to Hamilton's Harnack inequality for the Ricci flow on a 2-dimensional manifold with positive scalar curvature.
Keywords: Harnack inequality; heat equation; parabolic equation; Ricci flow; surface